2012
DOI: 10.1167/iovs.12-10410
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prostaglandin E2 (PGE2) Levels in Proliferative Diabetic Retinopathy, and Correlation with VEGF and Inflammatory Cytokines

Abstract: PGE(2) levels are significantly higher in the vitreous of patients with complications from proliferative diabetic retinopathy, and correlate with IP-10 and VEGF. The results of our study suggest that PGE(2) may have a pathogenic role in diabetic retinopathy and implicates a potential therapeutic role for nonsteroidal anti-inflammatory drugs. (ClinicalTrials.gov number, NCT01609881.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
99
0
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 33 publications
3
99
0
8
Order By: Relevance
“…Expression of the proinflammatory marker tumor necrosis factor alpha (TNF-␣) is elevated in the vitreous of patients with DR (32,33) and Müller cell specific disruption of VEGF inhibits diabetes-induced overexpression of TNF-␣ (24). Since diabetes failed to enhance VEGF in the retina of REDD1 knock-out mice, we also evaluated TNF-␣ expression.…”
Section: Ablation Of Redd1 Prevents Diabetes-induced Vegf Expression mentioning
confidence: 99%
“…Expression of the proinflammatory marker tumor necrosis factor alpha (TNF-␣) is elevated in the vitreous of patients with DR (32,33) and Müller cell specific disruption of VEGF inhibits diabetes-induced overexpression of TNF-␣ (24). Since diabetes failed to enhance VEGF in the retina of REDD1 knock-out mice, we also evaluated TNF-␣ expression.…”
Section: Ablation Of Redd1 Prevents Diabetes-induced Vegf Expression mentioning
confidence: 99%
“…3 In support of this, several studies have consistently shown elevated levels of inflammatory cytokines in the aqueous and vitreous of patients with proliferative DR (PDR) and diabetic macular edema. [4][5][6] Prostaglandins are an important class of inflammatory mediators that are biosynthesized from arachidonic acid by cyclooxygenase enzyme. 7 Nonsteroidal anti-inflammatory drugs (NSAIDs) are potent inhibitors of this enzyme and thereby the synthesis of all downstream prostaglandins.…”
mentioning
confidence: 99%
“…9,10 Prostaglandins are elevated in animal models of DR, and progression of retinopathy can be prevented or delayed with prostaglandin inhibitors. [11][12][13][14] A recent pilot study reported elevated vitreous levels of prostaglandin E 2 (PGE 2 ) in patients with PDR, 4 and several prospective clinical studies have reported favorable effects on DR with systemic NSAIDs. [15][16][17][18] In 2009, ketorolac tromethamine, 0.45% (Acuvail; Allergan Inc), was approved for pain and inflammation after cataract surgery.…”
mentioning
confidence: 99%
“…The most common interleukins found in DR patients are IL-6 and IL-8, where their concentrations were found increased in the vitreous of patients with PDR and prolonged hyperglycemia [3,42,47,[72][73][74][75][76][77][78][79][80][81][82]. Their role in the pathogenesis of PDR is still under investigation but evidence suggests the possibility of a rather direct contribution.…”
Section: Interleukinmentioning
confidence: 99%